High rate of hepatitis C reinfection following antiviral treatment in the North East England Prisons. Issue 4 (5th December 2019) - Bhandari, Rajan; Morey, Sarah; Hamoodi, Abi; Thompson, Craig; Jones, Dee; Hewett, Margaret; Hunter, Ewan; Taha, Yusri; McPherson, Stuart
Abstract: To achieve elimination of hepatitis C (HCV), a critical group to prioritise for diagnosis and treatment is the prison population, where HCV prevalence is high. A universal offer of blood‐borne virus testing (UOBBVT) programme and a new treatment pathway were introduced to seven North East England (NEE) Prisons. Our aim was to assess: (a) the proportion of individuals with active HCV commencing direct‐acting antivirals (DAAs); (b) the outcomes following DAA treatment; (3) the reinfection rate following sustained virological response (SVR). Data were collected prospectively on BBVT uptake, HCV positivity, HCV treatment outcomes and reinfection from March 2016 onwards. 8538 individuals had BBV testing. In total, 612 (7.2%) and 374 (4.4%) were HCV antibody positive and HCV RNA positive, respectively. Ultimately, 266 (71%) individuals commenced DAAs. Overall 111 achieved a documented SVR (42%), 17 (6%) failed treatment, 30 (11%) were still on treatment or had not reached 12 weeks post‐treatment at time of analysis, and 108 (41%) were lost to follow‐up. In those with a known outcome (n = 128), 87% achieved SVR. Worryingly, of those who achieved SVR, 21 (19%) were subsequently identified as having been reinfected (median time from SVR to documented reinfection 13 (range 7‐25) months). The reinfection rate was 0.406 cases per person‐year follow‐up. In conclusion, Implementation of a UOBBVT programme and new treatment pathway resulted in increased diagnosis and treatment of HCV in the NEE prison population. However, the high HCV reinfection rate suggests a need to improve harm reduction approaches.